2021
DOI: 10.1016/j.biopsych.2020.02.001
|View full text |Cite
|
Sign up to set email alerts
|

The β-Secretase BACE1 in Alzheimer’s Disease

Abstract: BACE1 (beta-site amyloid precursor protein cleaving enzyme 1) was initially cloned and characterized in 1999. It is required for the generation of all monomeric forms of amyloid-b (Ab), including Ab 42 , which aggregates into bioactive conformational species and likely initiates toxicity in Alzheimer's disease (AD). BACE1 concentrations and rates of activity are increased in AD brains and body fluids, thereby supporting the hypothesis that BACE1 plays a critical role in AD pathophysiology. Therefore, BACE1 is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
357
1
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 467 publications
(374 citation statements)
references
References 143 publications
9
357
1
7
Order By: Relevance
“…Neurogranin is a small neuron-specific and post-synaptic protein abundantly expressed in the brain, especially in the hippocampal and cerebrocortical dendritic spine [ 66 , 67 , 68 ]. Neurogranin has been found to play key roles in synaptic plasticity and long-term potentiation as a major regulator of the calcium-binding protein calmodulin and of calcium-signal transduction and memory formation [ 66 , 67 , 68 , 69 ]. Autopsy studies revealed a possible correlation between neurogranin and AD, as analyses showed reduced levels of neurogranin in brains and increased levels in the CSF of AD patients [ 68 ].…”
Section: Cerebrospinal Fluid Biomarkersmentioning
confidence: 99%
See 3 more Smart Citations
“…Neurogranin is a small neuron-specific and post-synaptic protein abundantly expressed in the brain, especially in the hippocampal and cerebrocortical dendritic spine [ 66 , 67 , 68 ]. Neurogranin has been found to play key roles in synaptic plasticity and long-term potentiation as a major regulator of the calcium-binding protein calmodulin and of calcium-signal transduction and memory formation [ 66 , 67 , 68 , 69 ]. Autopsy studies revealed a possible correlation between neurogranin and AD, as analyses showed reduced levels of neurogranin in brains and increased levels in the CSF of AD patients [ 68 ].…”
Section: Cerebrospinal Fluid Biomarkersmentioning
confidence: 99%
“…Moreover, it has been shown to be able to detect early-stage pathological changes, even in the MCI stage, and predict and monitor AD-related cognitive decline, thus serving as a promising pre-symptomatic biomarker [ 67 , 68 ]. BACE1 (β-site APP cleaving enzyme-1) is an aspartyl protease discovered in 1999, which, by contrast to other peptidases of the pepsin family, such as cathepsin D and E, is a type I transmembrane protein [ 69 , 71 ]. Commonly expressed in neurons, oligodendrocytes and astrocytes, BACE1 is more abundantly found within certain neuronal cell types [ 69 ].…”
Section: Cerebrospinal Fluid Biomarkersmentioning
confidence: 99%
See 2 more Smart Citations
“…The multicenter study conducted by Hulsteart et al established cutoff values of 1 for IATI (IATI < 1: Suggestive for AD; IATI > 1: Normal) and 61 ρg/mL for p-tau. Several authors then used these parameters in their studies, finding sensitivity values up to 94% in the diagnosis of AD; the lowest levels of specificity were found, however, in the diagnosis of VaD (48%) [ 26 ]. Within the population affected by AD there is a subgroup recognized as SNAP (suspected non-AD pathophysiology) [ 21 ], in which subjects have normal amyloid markers, but show signs of neurodegeneration different from AD.…”
Section: Classification and The Use Of New Biomarkers In Alzheimermentioning
confidence: 99%